Expressive arts therapy in group counseling: a systematic literature review - Suri, Gusni Dian; S, Neviyarni; Hariko, Rezki; Netrawati, Netrawati (Counseling and Humanities Review, 2025)
Expressive arts therapy, is a therapeutic approach that has been increasingly applied in various educational and mental health contexts. However, studies that specifically and systematically examine the application of expressive arts therapy within group counseling settings remain limited. This study aims to map and synthesize existing research findings on expressive arts therapy in the context of group counseling through a Systematic Literature Review (SLR). A total of 53 scholarly articles published between 2015 and 2025 were analyzed based on predefined inclusion and exclusion criteria. Bibliometric analysis using VOSviewer was conducted to identify thematic patterns, research trends, and conceptual linkages among topics. The findings indicate that previous studies have predominantly focused on creative arts therapy, expressive interventions, and psychosocial outcomes, while integration with the theoretical frameworks and practices of group counseling remains suboptimal. From a methodological perspective, most studies employed qualitative approaches, pilot studies, and program evaluations, whereas experimental studies and systematic reviews specifically addressing expressive arts therapy in group counseling are still scarce. These findings indicate the absence of an integrated model that incorporates expressive arts therapy into group counseling. This study therefore contributes by highlighting the need for the development of a more systematic and contextually grounded group counseling model based on expressive arts therapy.